2020
DOI: 10.1136/jitc-2020-000966
|View full text |Cite
|
Sign up to set email alerts
|

T-cell agonists in cancer immunotherapy

Abstract: Cancer cells can evade immune surveillance in the body. However, immune checkpoint inhibitors can interrupt this evasion and enhance the antitumor activity of T cells. Other mechanisms for promoting antitumor T-cell function are the targeting of costimulatory molecules expressed on the surface of T cells, such as 4-1BB, OX40, inducible T-cell costimulator and glucocorticoid-induced tumor necrosis factor receptor. In addition, CD40 targets the modulation of the activation of antigen-presenting cells, which ulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 110 publications
(137 reference statements)
2
44
0
Order By: Relevance
“…Notably, recent pre-clinical studies have shown that combination therapies aimed at enhancing such T-cell co-stimulating interactions improve anti-tumor immune responses even in low TMB and highly immuno-suppressive settings 3338 . Currently, several clinical trials to assess the safety and efficacy of these combinations are in progress 3942 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, recent pre-clinical studies have shown that combination therapies aimed at enhancing such T-cell co-stimulating interactions improve anti-tumor immune responses even in low TMB and highly immuno-suppressive settings 3338 . Currently, several clinical trials to assess the safety and efficacy of these combinations are in progress 3942 .…”
Section: Discussionmentioning
confidence: 99%
“…3A interactions improve anti-tumor immune responses even in low TMB and highly immunosuppressive settings [32][33][34][35][36][37] . Currently, several clinical trials to assess the safety and efficacy of these combinations are in progress [38][39][40][41] .…”
Section: Tumors With Dna Mismatch Repair Deficiency Have Heightened Tmentioning
confidence: 99%
“…Anti-CTLA-4 ICB, for instance, supports the induction phase of anti-tumor T cell responses, while ICB that targets the PD-1/PD-L1 axis serves mainly to maintain the effector phase of anti-tumor T cell responses. Therefore, the mixture of anti-CTLA-4 and anti-PD-1/PD-L1 therapies not only showed synergistic effects in pre-clinical models but also increased their efficacy compared to monotherapies in clinical settings such as in patients with metastatic melanoma and advanced renal cell carcinoma [ 26 , 27 ]. However, parallel with clinical effectiveness, there was an increase in the frequency of immune-related adverse events (irAE) with combinatorial ICB regimens [ 28 ].…”
Section: Current State Of Tumor Immunologymentioning
confidence: 99%
“…An alternative approach to mobilize tumor-specific T lymphocytes against cancer comprises the activation of co-stimulatory pathways by agonists [ 27 ]. The major co-stimulatory pathway, often referred to as the second signal of T lymphocyte activation, involves CD28 engagement by CD80/86.…”
Section: Current State Of Tumor Immunologymentioning
confidence: 99%
“…Full T cell activation requires three key signals: engagement of T cell receptors by antigen peptide-bound major histocompatibility complex, ligation of co-stimulatory molecules, and support from cytokines [1]. In addition, recent studies have stressed a cardinal role of co-inhibitory molecules in regulating excessive T cell activation [2][3][4][5]. There are several co-stimulatory and co-inhibitory molecules, also known as immune checkpoint molecules (Figure 1).…”
Section: Introductionmentioning
confidence: 99%